Treatment Outcomes among People Living with HIV Who are Food Insecure and Prescribed Antiretrovirals that Require Food - Kalichman, Seth C. (J Prim Care Community Health, 2014)
BACKGROUND: Food insecurity is a known barrier to medication adherence among people living with HIV. Antiretroviral therapies (ART) that require food for maximum benefit likely pose added challenges to patients who do not have reliable access to food. This study examines the health implications of prescribing ART that requires food to patients who are food insecure. METHOD: A community sample of 538 men and 221 women currently taking ART to treat their HIV infection completed computerized interviews, biweekly-unannounced pill count adherence assessments, and obtained their CD4 cell count and HIV RNA from medical records. RESULTS: Sixty-three percent of participants experienced at least one indicator of food insecurity during the previous month, of which 274 (57%) were prescribed an ART regimen that requires food. Among participants who were food insecure, individuals taking ART requiring food indicated significantly greater HIV symptoms, lower CD4 cell counts, and poorer HIV suppression. For participants who were food secure, those taking ART that requires food were significantly less adherent than those whose ART regimen does not require food. CONCLUSIONS: People living with HIV who experience food insecurity are significantly more likely to be prescribed ART regimens that require food and experience poorer treatment outcomes. Determination of optimal ART regimens should take patient access to food into account and treatment guidelines should highlight the importance of food access in selecting ART regimens.